Unlocking the paracetamol adsorption mechanism in graphene tridimensional-based materials: an experimental-theoretical approach - de Matos, Carolina F.; Leão, Mayara B.; Vendrame, Laura F. O.; Jauris, Iuri M.; Zanella, Ivana; Fagan, Solange B. (Frontiers in Carbon, 2024)
The omnipresence of emerging contaminants in the aquatic environment is indisputable. These contaminants include chemical substances not removed in traditional water and sewage treatment processes. To ensure the quality of water and healthy aquatic ecosystems, new treatment technologies and materials are essential to effectively control the presence of these contaminants in the aquatic environment. More than that, it is important to know how molecules interact with these new materials.A low-cost alternative currently available is adsorption. Despite this method being widely studied, describing the interaction mechanisms between the materials and the analytes is not usual, limiting the obtainment of more efficient materials. Thus, the objective of this work was to understand, in a theoretical-experimental way, the forms of interaction in the adsorption of the drug paracetamol, widely used worldwide, in materials based on graphene with different chemical and structural properties. For this, kinetic and isothermal experimental studies were carried out using four materials that contemplated different dimensions, pore sizes, and oxidation degrees. In theoretical studies, density functional theory (DFT) simulations were performed to cover quantum details, revealing how paracetamol interacts with different graphene structures. According to theoretical studies, binding energies, binding distances, and charge transfer between oxidized graphene and PCM drug are compatible with physical adsorption, strongly dependent on the type and number of functional groups on the graphene surface. These results agree with the experimental data where the highest adsorptions were observed precisely for materials containing a higher proportion of functional groups and where these groups are more available (more porous), with adsorptive capacities reaching 235.7 mg/g. Our findings contribute to scientific knowledge about using graphene structures as an adsorbent material, providing a solid basis for future studies and developing more efficient and advanced water treatment technologies.